Close reading strategy to analize fake news and historical evidences about the Holocaust in Secondary Education - Moreno-Vera, Juan Ramón; Gómez-Carrasco, Cosme Jesús; ´González-Chicote, Félix (Investigaciones Sobre Lectura, 2025)
The study aims to analyse the ability of high school students to distinguish fake news through the careful reading of historical sources, in this case, about Holocaust denialism. Access to a multitude of sources via the internet has meant that our students are also exposed to a large amount of fake or biased news. It is often difficult for them to assess the reliability of a source, and comparing sources, which is part of the historian’s method, becomes a very powerful strategy. In fact, the participating high school students showed very positive results when the activity is guided by the questions of close reading of the sources.